Analisis Penerapan Balanced Scorecard Untuk Mengukur Kinerja Perusahaan Pada Pt. Xyz Tbk. - Sudiman Sudiman (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The Balanced Scorecard has been shown to be a valuable tool for management control in organization, particulary in the current context where continuous improvement of results and level of quality is demanded in both the private and public spheres. The Balanced Scorecard is a measurement and management system that views a business unit’s performance from four perspectives includes financial, customer, internal business process, and learning and growth.This research was analyzed using Balanced Scorecard Analysis, Liquidity Ratio Analysis, PEST Analysis and SWOT Analysis. The Analysis to explore more detail about the measurement of business performance from four perspectives includes financial, customer, internal business process, and learning and growth at PT. XYZ Tbk. This research concludes that Balanced Scorecard measurement gives the company more detail about its business performance, and enable the company to create strategies which linked in Balanced Scorecard perspectives in term to increase stakeholders value.